Transition Readiness of Pediatric Sickle Cell Patients to Adult Clinic in a Teaching Hospital, Ghana - Aaron Kwasi Nartey; Vivian Paintsil; Isaac Nyanor; Yaa Gyamfua Oppong-Mensah; Evans Xorse Amuzu; Eunice Agyeman Ahmed; Suraj Yawnumah Abubakar; Alex Osei-Akoto (Advances in Hematology)
Conclusion: The study revealed a high transition readiness among pediatric patients. In general, the patients had high confidence transitioning to an adult clinic and the ability to manage their own healthcare. However, patients were hesitant speaking about their SCD status. Staying with both parents was significantly associated with higher scores for appointment keeping. Also, staying with other relations significantly reduced the scores for medication management. We recommend setting up of an adolescent sickle cell support group to help reduce stigmatization and improve health outcomes.